Gamification effects on users' motivation to contribute knowledge in a Portuguese Q&A community - Oliveira Jordao do Amaral, Isabel; Kang, Minhyung (Aslib Journal of Information Management, 2021)
Purpose: This research investigates the detailed mechanisms of how gamification affordances influence intrinsic and internalized extrinsic motivation and ultimately improve the quality and quantity of knowledge contribution. Design/methodology/approach: Survey responses from 154 users of Stack Overflow in Portuguese were analyzed by the partial least squares–structural equation modeling approach to validate the research model. Findings: Challenge and goal setting influence individuals to reach the flow state, which increases the quantity of knowledge contribution. Rewards enhance the quality of knowledge contribution through perceived self-worth. Social comparison increases perceived reputation, but its impact does not ultimately lead to knowledge contribution. Originality/value: The current study differentiated types of motivation and dimensions of knowledge contribution when exploring the effects of gamification affordances. This perspective was proven helpful to understand the various gamification affordances' influence on knowledge contribution.
Keywords: Design/methodology/approach; Extrinsic motivation; Goal setting; Knowledge contributions; Partial least square (PLS); Research models; Stack overflow; Structural equation modeling; Gamification; Knowledge contribution; Motivation; Q&A community; Self-determination theory; Stack exchange